Numerical Investigation of Aluminum Fumarate MOF adsorbent material for adsorption desalination/cooling application. (December 2017) - Youssef, Peter; Mahmoud, Saad; Al-Dadah, Raya; Elsayed, Eman; El-Samni, Osama
Abstract: A metal organic frame work (MOF) material called Aluminum Fumarate is numerically investigated for adsorption desalination/cooling applications in a 2-bed system and compared to silica-gel and AQSOA-Z02. Effect of evaporator and desorber bed water temperatures on cycle specific daily water production, specific cooling power and overall conversion ratio has been studied. Water temperatures ranges are (10-30°C) for evaporator and (65-85°C) for desorbing bed. It was found that for all materials, as evaporator water temperature increases, water production and cooling capacity increase. Moreover, heating source temperature has little impact on cycle performance with Al-Fumarate while when silica-gel or AQSOA-Z02 is used; cycle performance degrades dramatically with lower heating temperatures. Results showed that at 85°C hot water and 30°C evaporator and bed cooling water temperatures, Al-Fumarate can produce 11.3m 3 /tonne.ads/day of water and 90.9Rton/tonne.ads of cooling while AQSOA-Z02 and silica-gel produce 6.4 and 8.4m 3 of water/day and cooling of 50.5 and 62.4Rton per tonne.ads respectively. Furthermore, at low bed heating water temperature of 65°C and 10°C evaporator water temperature, Al-Fumarate results in 3.4m 3 of water/day and 20Rton per tonne which is 345% and 200% higher than AQSOA-Z02 and silica-gel. Therefore, Al-Fumarate has a potential in adsorption desalination-cooling applications specially at low desorption temperaures.